Profile of Sepsis Patients Treated in Intensive Care Unit of Sanglah Hospital Denpasar - Merry, Merry; Hartawan, I Gusti Agung Gede Utara; Aryabiantara, I Wayan; Dewi, Dewa Ayu Mas Shintya (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Primary data regarding sepsis patients in Indonesia, especially in Denpasar, are still limited in number in reporting. The lack of information about sepsis made the authors interested in conducting this study. AIM: The aim of the study was to obtain more in-depth information about the profile of sepsis patients treated in Sanglah Hospital, Denpasar. MATERIALS AND METHODS: This was a cross-sectional descriptive research. Target population in this study are data on patient registers that are included in the inclusion criteria from June 1, 2019 to June 30, 2021, at intensive care unit Sanglah Hospital, Denpasar. The variables in this study included: Demographic conditions such as age, gender, and address, qSOFA score, comorbidities, ventilator, and patient’s outcome (survival or non-survival). RESULTS: A total samples were 173 patients. The average age of patients in this study was 54 years old with 56.6% male and 32.9% lived in Denpasar. Patients suspected of having early sepsis had a qSOFA 0 score of 35.3%, qSOFA 1 was 33.5%, qSOFA 2 was 23.7%, and qSOFA 3 was 7.5%. Patients with sepsis and suspected sepsis with comorbidities were 96% and 79.8% of patients were on a ventilator. The mortality rate in this study was 67.1%. CONCLUSION: These primary data hopefully become references for the future research.